Motyw drabiny Jakubowej (Rdz 28,10-22) w starożytnej symbolice zachodniego chrześcijaństwa - Bardski, Krzysztof (Collectanea Theologica, 2019)
The episode of “Jacob’s ladder” in the book of Genesis inspired numerous symbolic interpretations in ancient Christianity. Most often we find moral symbolism, which basically proceeds in two directions. After Tertullian, “descending angels” symbolise sinners, and “ascending” ones symbolise righteous people. After Augustine, “descending” means those who care about the needs of others, whilst “ascending” refers to those who direct their hearts to God. For Jerome, ascending and descending angels symbolise not so much people as the mercy of God who descends to the sinner, whereas for Ambrose and Zeno of Verona the ladder depicts the Old and New Testament and its rungs, namely the Christian virtues. An important literary motif in the story of “Jacob’s ladder” is the stone under the Patriarch’s head, which in the Christian tradition assumes a Christological meaning.